Atividade física e gastos com medicamentos entre hipertensos atendidos em diferentes modalidades da atenção primária - Guiça, Juziane Teixeira [UNESP]; Correia, Dayane Cristina Queiroz [UNESP]; Rodrigues, Charles [UNESP]; Fernandes, Romulo Araújo [UNESP]; Norberto, Maria Carolina Castanho Saes [UNESP]; de Lima Rodrigues, Glória [UNESP]; Codogno, Jamile Sanches [UNESP] (FapUNIFESP (SciELO), 2025)
The aim is to compare the level of physical activity and medication expenditures of hypertensive patients treated in different types of primary health care in the city of Presidente Prudente. People of both sexes participated, aged ≥ 40 years, registered in three health different approaches: Primary Care, Primary Care+ e Primary Care+PE. Data on physical activity, illness and medication expenditures was obtained by telephone interview and consultation of the electronic medical record. The chi-square test, Kruskal-Wallis and linear regression were used. The statistical significance adopted was 5%. A total of 659 people were evaluated, with a mean age of 62 years. It was observed that between the modalities, the presence of diseases was higher in patients attended by the Primary Care+PE. Analyzing physical activity and medication expenses, a negative relationship can be observed in the Primary Care+ (r = -0.149; CI = -0.277 to -0.016) and Primary Care+PE (r = -0.210; CI = -0.334 to -0.079), after adjusting for gender, age, body mass index and sum of diseases, only the Primary Care+PE modality remained significant. The Primary Care+PE was the only modality to present lower expenses with medication for more physically active patients, even after adjusting for confounding variables.